Collapse Settlement Prediction of Footings Built over Natural and Compacted Soils - Rodrigues, Roger Augusto [UNESP]; Prado Soares, Fabio Visnadi [UNESP]; Sanchez, Marcelo (American Society of Civil Engineers (ASCE), 2022)
Collapsible unsaturated soils experience large volumetric compressive deformations upon wetting. Compaction is a simple and effective soil improvement technique that could significantly reduce soil collapsibility. This paper deals with the numerical modeling of effect of soil compaction on collapsible-soils settlements upon wetting under field conditions. The finite elements program CODE_BRIGHT was adopted for the numerical simulation of field tests using the model parameters that were previously obtained from independent laboratory experiments. The numerical simulations show that the proposed approach is able to model the behavior observed in the in situ tests involving footing prototypes on collapsible-soils subjected to soaking.